Revitalisasi Sastra Lokal dan Islami melalui Aplikasi Bercerita Digital Bilingual - Nuraini, Anisa; Wahidah, Nurul; Sukardi, Sukardi (SENTRI: Jurnal Riset Ilmiah, 2025)
The persistent problem of low literacy among Indonesian students, as highlighted by PISA 2018, underscores the urgency of innovative approaches to literacy education. Local and Islamic literature holds rich cultural and moral values that can contribute to character building and contextual learning, yet its transmission remains dominated by oral and printed forms that are less appealing to the digital native generation. This study aimed to explore the adaptation of local and Islamic narratives into a bilingual (Indonesian–English) digital storytelling application to enhance literacy skills in elementary school students. Employing a Research and Development (R&D) approach with the ADDIE model, the research focused on the Analysis and Design phases, with an initial step into Development. Data collection was carried out through literature review, interviews with cultural and religious figures, and participatory classroom and community observations. By the 80% stage of completion, the study produced a documented inventory of Lombok–Bima folk and Islamic stories, adaptive bilingual drafts of selected narratives (Cupak Gerantang, Tegodek Godek, and Prophet Ibrahim), and a mock-up design of the digital application featuring bilingual text, illustrations, and simple navigation. Preliminary validation from teachers, cultural experts, and literacy practitioners indicates that bilingual digital media rooted in local culture and Islamic values can effectively increase student engagement and support literacy growth. These findings highlight the novelty of integrating cultural heritage into modern bilingual digital platforms, offering a contextual solution to literacy challenges and contributing to sustainable character education in the digital era)